Odpowiedzi

Najlepsza Odpowiedź!
2010-01-21T19:18:50+01:00
Y=2x-4
3x-y=1

y=2x-4
3x-2x+4=1

y=2x-4
x=-3

y=-10
x=-3

b)
2x-2y=7
4x+3y=21

2x=7+2y
4(7/2+y)+3y=21

2x=7+2y
14+4y+3y=21

2x=7+2y
7y=7

2x=7+2y
y=1

2x=7+2
y=1

x=4
y=1

c)
2x+6y=15
3x-6y=25

2x=15-6y
3(15/2-3y)-6y=25

2x+6y=15
45/2-9y-6y=25

2x+6y=15
-15y=5/2

2x+6y=15
y=-1/6

2x+6(-1/6)=15
y=-1/6

2x=16
y=-1/6

x=8
y=-1/6
1 4 1
2010-01-21T19:24:43+01:00

a)3x-2x+4=1
x = -3
y=-10

b)2x-7=2y => y= x-7/2
4x+3(x-7/2)=21
7x=49/2
x=7/2
y=0

c)x=15/2-3y
3(15/2-3y) -6y=25
45/2-9y-6y=25
95/2=15y
y=95/30=19/6
x=15/2-270/30 = 7,5 -9 = -1,5
2 1 2